OpenRAN a new architecture for mobile wireless Internet radio access networks. - Kempf, J. (IEEE Communications magazine)
Cellular telephony networks depend on an extensive wired network to provide access to the radio link. The wired network, called a radio access network, provides such functions as power control and, in CDMA networks, combination of soft handoff legs (also known as macrodiversity resolution) that require coordination between multiple radio base stations and multiple mobile terminals. Existing RAN architectures for cellular systems are based on a centralized radio network controller connected by point-to-point links with the radio base transceiver stations. The existing architecture is subject to a single point of failure if the RNC fails, and is difficult to expand because adding an RNC is expensive. Also, although a network operator may have multiple radio link protocols available, most RAN architectures treat each protocol separately and require a separate RAN control protocol for each. We describe a new architecture, the OpenRAN architecture, based on a distributed processing model with a routed IP network as the underlying transport fabric. OpenRAN was developed by the Mobile Wireless Internet Forum IP in the RAN working group. The OpenRAN architecture applies principles to the radio access network that have been successful in reducing cost and increasing reliability in data communications networks. The result is an architecture that can serve as the basis for an integrated next-generation cellular radio access network.